HVAC troubleshooting guide [ - Miller, Rex , 1929- (McGraw Hill, 2009)
"Applicable to residential, commercial, and industrial jobs, this essential handbook puts a wealth of real-world information at your fingertips. HVAC Troubleshooting Guide shows you how to read, interpret, and prepare schedules, mechanical plans, and electrical schematics. This handy resource will aid you in your everyday tasks and keep you up to date with the latest facts, figures, and devices. The book includes numerous illustrations, tables, and charts, troubleshooting tips, safety precautions, resource directories, and a glossary of terms."--Jacket.